Kilka uwag o sądach tajnych stalinowskiej Polski - Bojko, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Communism in Poland at its initial stage was the time of great persecutions and repressions against everyone who opposed the new authority established by the Soviets. Law and courts became obedient instruments in the hands of Communists, aiming to eliminate their political enemies and intimidate Polish society. Secret courts had a particular role to play in this undertaking. In this article the author, based on the selected literature, characterized the origin of secret courts, their organizational structure and activity. The paper also briefly describes the major figures involved in secret courts.
Keywords: “Nil” Fieldorf; secret courts; secret sections; court crimes; communism